Computer vision system (CVS) for color and surface oil measurements of durian chips during post‑frying - Udomkun, Patchimaporn; Innawong, B.; Jeepetch, K. (Springer, 2019)
This study aimed to investigate the feasibility of using the computer vision system (CVS) for monitoring color and surface oil content of durian chips during post-frying cooling. The results revealed the browning index values increased with cooling time, while surface oil content decreased. A high linear correlation of browning index as well as surface oil content and cooling time was observed (R2 > 0.92). The image-processing technique can effectively be used to describe browning index and surface oil content of fried durian chips as it yielded a very high correlation (R2 > 0.94). This technology exhibits great potential as a reliable, rapid, consistent, and non-destructive tool for process optimization and quality control of fried products.